(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Hypothermia is a common complication but has not received adequate attention in patients undergoing continuous renal replacement therapy (CRRT). Objective:To determine the prevalence and several factors associated with hypothermia in patients undergoing continuous renal replacement therapy at the Intensive Care and Toxicology Department and the Surgical Intensive Care Unit of Saint Paul General Hospital. Methods: A prospective descriptive study was conducted on 67 patients indicated for continuous renal replacement therapy (CRRT). Results: The incidence of hypothermia during continuous renal replacement therapy (CRRT) was 29.8% (20 patients). Among patients who developed hypothermia, the majority experienced moderate (34.0–<35.0°C) or severe hypothermia (<34.0°C). Patients with fever prior to CRRT had significantly higher odds of developing hypothermia than those without prior fever (OR = 3.92; 95% CI: 1.16–13.7). This association was statistically significant (p = 0.027). Conclusion: The proportion of patients undergoing dialysis who experienced hypothermia at Xanh Pôn General Hospital in 2026 was 29.8% (20 patients). This rate of hypothermia in the study is noteworthy and consistent with the observation that CRRT can increase heat loss through extracorporeal circulation, particularly in critically ill patients. However, direct comparisons with other studies should be made cautiously due to differences in the definition of hypothermia, temperature measurement sites, patient characteristics, and warming protocols during CRRT.